Investigating applied drought in Miscanthus sinensis; sensitivity, response mechanisms, and subsequent recovery. Issue 7 (21st April 2022) - Al Hassan, Mohamad; van der Cruijsen, Kasper; Dees, Dianka; Dolstra, Oene; Trindade, Luisa M.
Abstract: Miscanthus is renowned for its excellent water‐use efficiency and good adaptability to a wide range of environmental conditions, making it suitable for cultivation on marginal soils. Drought is a major cause of this marginality, and its occurrence is becoming more frequent and prolonged due to climatic change. Developing drought tolerant genotypes of miscanthus would ensure the maintenance of economically viable yields on lands prone to periodic water‐deficiency. To better understand the underlying response and tolerance mechanisms, pre‐screen for better survivability at plot setup on marginal lands, and identifying early biomarkers of stress, we explored the genetic diversity present in Miscanthus sinensis under applied drought. Young plants of 23 genotypes underwent 3 weeks of water‐deprivation in glasshouse‐controlled conditions, followed by an equal period of recovery. Leaves harvested at the end of both experimental phases were the focus of extensive biochemical analyses. Coupled with monitoring several growth and yield parameters, this was instrumental in evaluating stress impact and responses. The most productive genotypes suffered the most in terms of yield reduction and chlorophyll degradation when stress was applied. In parallel, proline and simple soluble sugars accumulated to readjust the osmotic potential in the cytosol and vacuoles, respectively. The necessary carbon skeletons for this buildup were partially acquired from resources diverted away from cell wall synthesis and maintenance, whose content dropped under stress in parallel to increasing drought‐sensitivity. Correspondingly, expressional and biochemical analyses revealed a dynamic turnover of starch and soluble sugars in stressed leaves. Meanwhile, better avoidance of stress enabled a more efficient post‐drought recovery, which was characterized by restoring pre‐stress hydraulic status and unplugging stress response mechanisms. Abstract : In the presented work, we investigated the impact and response mechanisms to drought and its subsequent recovery in Miscanthus sinensis . Three weeks of applied stress caused a disruption of vegetative growth, evident in reduced yield, notably in the more productive genotypes. Osmolytes accumulated in the cytoplasm and vacuoles, as a result to readjust the faltering osmotic potential. This buildup, however, came at the expense of other carbon‐demanding pathways such as cell wall synthesis and maintenance, whose content dropped under stress. Meanwhile, restoring pre‐stress hydraulic status and shutting down stress response mechanisms were characteristic of early post‐drought recovery. The graphical abstract was formulated using biorender.com (2022), accessed from https://app.biorender.com/biorender‐templates .